Math, asked by gurmansaini6079, 1 year ago

Find the value of expression tan  \bigg(\frac{sin^{-1}  x+ cos^{-1}x}{2} \bigg) , when \ x=\frac{\sqrt{3}}{2}

Answers

Answered by Swarup1998
71
\underline{\underline{\text{Solution :}}}

\underline{\text{Method 1}}

\mathrm{Now,\:\frac{sin^{-1}x+cos^{-1}x}{2}}

\mathrm{=\frac{sin^{-1}\frac{\sqrt{3}}{2}+cos^{-1}\frac{\sqrt{3}}{2}}{2}}

\mathrm{=\frac{\frac{\pi}{3}+\frac{\pi}{6}}{2}}

\mathrm{=\frac{1}{2}*\frac{2\pi+\pi}{2}}

\mathrm{=\frac{1}{2}*\frac{3\pi}{6}}

\mathrm{=\frac{\pi}{4}}

\to \boxed{\mathrm{\frac{sin^{-1}x+cos^{-1}x}{2}=\frac{\pi}{4}}}

\underline{\text{Method 2}}

\mathrm{Now,\:\frac{sin^{-1}x+cos^{-1}x}{2}}

\mathrm{=\frac{1}{2}*\frac{\pi}{2}}

\mathrm{=\frac{\pi}{4}}

\to \boxed{\mathrm{\frac{sin^{-1}x+cos^{-1}x}{2}=\frac{\pi}{4}}}

\underline{\text{Rules :}}

\mathrm{1.\:sin^{-1}x+cos^{-1}x=\frac{\pi}{2}}

\mathrm{2.\:sin^{-1}\frac{\sqrt{3}}{2}=\frac{\pi}{3}}

\mathrm{3.\:cos^{-1}\frac{\sqrt{3}}{2}=\frac{\pi}{6}}

\underline{\text{Extra :}}

\text{We know that,}

\mathrm{sin\frac{\pi}{3}=\frac{\sqrt{3}}{2}}

\to \mathrm{\frac{\pi}{3}=sin^{-1}\frac{\sqrt{3}}{2}}

\to \mathrm{sin^{-1}\frac{\sqrt{3}}{2}=\frac{\pi}{3}}

smiley91: yepp aur to aur comment section is also for correcting the answerer irrespecting they are mods or kuchbhi ho
smiley91: ooyy ache se baat ki to ache se rha chachi group se pa ga na le
smiley91: i know but think so you don't know ask.... kyu gali khane ke mood me he me gaali nhi dta
Similar questions